Advances in Process Metallurgy - Peng, Hong; Forsberg, Kerstin (JOM (1989), 2021)
In their article "Structural Characteristics of CaO-SiO2-Al2O3-FeO Slag with Various FeO Contents based on Molecular Dynamics Simulation," simulated data indicating that, as the FeO content increases, the diffusion coefficient of each atom increases, and the system viscosity decreases. [...]six papers cover secondary resource utilization. The results indicated that CuO could be reduced to the metal via a tire (rubber) pyrolysis route in the temperature range 700-900 K. "Comparison of Biomass and Coal in Recovery Process of Silicon in an Electric Arc Furnace" by H. Hasannezhad and A. Meysami, (published in April) studied the silicon recovery of silica ore (SiO2) in an electric arc furnace using two types of carbon materials: charcoal as a biomass and coal as a fossil fuel.